Computational Evaluation of B-Cell Clone Sizes in Bulk Populations - Rosenfeld, Aaron M.; Meng, Wenzhao; Chen, Dora Y.; Zhang, Bochao; Granot, Tomer; Farber, Donna L.; Hershberg, Uri; Luning Prak, Eline T. (Frontiers in Immunology, 2018)
B cell clones expand and contract during adaptive immune responses and can persist or grow uncontrollably in lymphoproliferative disorders. One way to monitor and track B cell clones is to perform large-scale sampling of bulk cell populations, amplifying and sequencing antibody gene rearrangements by next generation sequencing (NGS). Here we describe a series of computational approaches for estimating B cell clone size in NGS immune repertoire profiling data of antibody heavy chain gene rearrangements. We define three different measures of B cell clone size-- copy numbers, instances and unique sequences-- and show how these measures can be used to rank clones, analyze their diversity and study their distribution within and between individuals. We provide a detailed, step-by-step procedure for performing these analyses using two different data sets of spleen samples from human organ donors. In the first data set, 19 independently generated biological replicates from a single individual are analyzed for B cell clone size, diversity and sampling sufficiency for clonal overlap analysis. In the second data set, B cell clones are compared in 8 different organ donors. We comment upon frequently encountered pitfalls and offer practical advice with alternative approaches. Overall, we provide a series of pragmatic analytical approaches and show how different clone size measures can be used to study the clonal landscape in bulk B cell immune repertoire profiling data.